Pengaruh Kualitas Makanan dan Suasana Restoran Terhadap Keputusan Berkunjung Kembali Melalui Kepuasan Pelanggan di Restoran Parle Senayan - Harsono, Arif Agus; Ingkadijaya, Rahmat; Ratu Bilqis, Linda Desafitri; Rahmanita, Myrza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
JJakarta as a thriving center of modern culinary culture, continues to introduce dining spaces that offer more than just food delivering a complete and memorable experience instead. Parle Senayan stands as a prime example, presenting high quality Indonesian cuisine complemented by an elegant and luxurious atmosphere. This study was conducted to identify the key factors that most strongly influence customers’ decisions to revisit the restaurant. Based on an analysis of 400 customers using SEM PLS, the findings reveal compelling evidence that both food quality and restaurant atmosphere have a direct and significant role in driving revisit intentions. Consistent flavor, fresh ingredients, and a comfortable, refined environment were shown to enhance customers’ desire to return. However, customer satisfaction does not directly determine revisit decisions; rather, it functions as an intermediary that strengthens the influence of food quality and atmosphere on consumer behavior. These results indicate that for premium restaurants, delivering an outstanding dining experience is not only essential but also a crucial strategy for maintaining visitor loyalty. Keywords: customer satisfaction, food quality, restaurants, restaurant atmosphere, revisit decisions